MEWUJUDKAN CHEKS AND BALANCES DALAM PENYUSUNAN UNDANG UNDANG - Sulardi Sulardi (Faculty of Law, Universitas Diponegoro, 2013)
ABSTRACT The doctrine of separation of power and checks and balances in principle can be applied in a presidential system of government as a real son and only child of the doctrine of separation of powers, because outside the presidential system of government, the power of the institutions of power tend to be model of power sharing. Constitution of the Republic of Indonesia in 1945 claimed to carry system presidential administration. The consequences of the choice of a presidential system of government, the application of separation of power in which checks and balances spirit was necessary.RI State Constitution of 1945 explicitly have separation of power in each of the executive, legislative and judicial. However, in line with the Regional Representatives Council, in addition to the House of Representatives raises issues relating to the authority of the Regional Representatives Council legislation and mechanisms of power drafting legislation.Regional Representatives Council, as the representative body of the people did not fully have the legislative authority than the authority vested in the House of Representatives. But the President as the executive actually has greater power in the preparation of legislation. Strengthening the presidential system of government with the authority to rearrange the Regional Representative Council, the House of Representatives and the President as well as overhauling the laws of mechanics are alternative ideas in order to realize checks arranging and balances in the legislation. Keywords: presidential system, separation of powers, checks and balances. Abstraksi Doktrin pemisahan kekusaan dan cheks and balances secara prinsip dapat diterapkan dalam sistem pemerintahan presidensiil sebagai anak kandung dari doktrin pemisahan kekuasaan itu, sebab di luar sistem pemerintahan presidensiil, kekuasaan dalam lembaga kekuasaan cenderung menganut model pembagian kekuasaan. UUD Negara Republik Indonesia tahun 1945 mengklaim melaksanakan sisitem pemerintahan presidensiil. Konsekuensi atas pilihan sistem pemerintahan presidensiil ini, penerapan pemisahan kekusaan yang di dalamnya mengandung semangat cheks and balances merupakan suatu keniscayaan. UUD Negara RI tahun 1945 secara ekplisit telah melakukan pemisahaan kekuasaan pada masing masing lembaga eksekutif, legislatif dan yudikatif. Akan tetapi seiring dengan adanya Dewan Perwakilan Daerah, di samping Dewan Perwakilan Rakyat memunculkan masalah terkait dengan kewenangan legislasi Dewan Perwakilan Daerah dan mekanisme kekuasaan penyusunan undang-undang. Dewan Perwakilan Daerah, sebagai lembaga perwakilan rakyat ternyata tidak sepenuhnya mempunyai kekuasaan legislasi dibandingkan dengan kewenangan yang ada pada Dewan Perwakilan Rakyat. Akan tetapi Presiden selaku lembaga eksekutif justru mempunyai kekuasaan yang besar dalam penyusunan undang-undang. Kata kunci : Sistem presidensiil, pemisahan kekuasaan, cheks and balances.